The relationship between customer satisfaction and customer retention at Sports Direct Seremban / Mohamad Mukri Nabil Azmi ... [et al.]. - Azmi, Mohamad Mukri Nabil; Linoby, Adam; Md Yusoff, Yusandra; Haziq, Amrun; Zulqarnain, Muhammad; Sazali, Razif (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Customer retention is essential for sustained success, particularly in competitive marketplaces. This study examines the correlation between customer satisfaction and client retention at Sports Direct Seremban, emphasising pricing, product services, and critical aspects affecting retention. This research is designed to clarify consumer loyalty processes to offer practical insights for improving customer happiness and promoting retention in the evolving sports retail sector. A structured questionnaire adapted from previous study, was used to collect data from 118 customers of Sports Direct Seremban [7]. The questionnaire included demographic details and sections evaluating price, product services, and customer retention using a 5-point Likert scale. Data were analyzed with SPSS version 27 to determine key correlations and insights, ensuring reliability and relevance to the study objectives.